2019
DOI: 10.18203/2349-2902.isj20191901
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing fasciitis: diagnostic and prognostic value of laboratory risk indicator for necrotizing fasciitis score

Abstract: Background: Necrotizing fasciitis (NF) is a potentially life threatening disease. Delayed recognition and surgical intervention is directly linked to increased mortality. Laboratory risk indicator for necrotizing fasciitis (LRINEC) score, a laboratory oriented tool has potential to prevent morbidity and mortality but there exhibits a controversy regarding its utility which needs re-evaluation to prove it’s utility.Methods: A tertiary care hospital based observational study aims to evaluate diagnostic and progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A study conducted by Wong et al [ 16 ] showed erythema (100%), pain (98%), bullae (45%), necrosis (14%), fever (53%), and hypotension (18%). Pain and swelling were the main presenting symptoms of NF in the study conducted by Soitkar et al [ 17 ]. Fever was the next most common symptom observed in 90% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Wong et al [ 16 ] showed erythema (100%), pain (98%), bullae (45%), necrosis (14%), fever (53%), and hypotension (18%). Pain and swelling were the main presenting symptoms of NF in the study conducted by Soitkar et al [ 17 ]. Fever was the next most common symptom observed in 90% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…30 Multiple studies validated the LRINEC scoring and found a significant statistical correlation between LRINEC and true diagnosis of NF. [33][34][35] A few reported not only the reliability of LRINEC scoring in diagnosing NF but also the higher score correlating with higher SOFA score, prolonged hospital stay, prolonged ICU stay, and mortality. They also added that LRINEC had a decreased sensitivity in immunocompromised patients.…”
Section: Laboratory Parametersmentioning
confidence: 99%